Modulation of intrinsic brain activity by electroconvulsive therapy in major depression - Leaver, Amber M. (Biol Psychiatry Cogn Neurosci Neuroimaging, 2016)
INTRODUCTION: One of the most effective interventions for intractable major depressive episodes is electroconvulsive therapy (ECT). Because ECT is also relatively fast-acting, longitudinal study of its neurobiological effects offers critical insight into the mechanisms underlying depression and antidepressant response. Here we assessed modulation of intrinsic brain activity in corticolimbic networks associated with ECT and clinical response. METHODS: We measured resting-state functional connectivity (RSFC) in patients with treatment-resistant depression (n=30), using functional magnetic resonance imaging (fMRI) acquired before and after completing a treatment series with right-unilateral ECT. Using independent component analysis, we assessed changes in RSFC with 1) symptom improvement and 2) ECT regardless of treatment outcome in patients, with reference to healthy controls (n=33, also scanned twice). RESULTS: After ECT, consistent changes in RSFC within targeted depression-relevant functional networks were observed in the dorsal anterior cingulate (ACC), mediodorsal thalamus (mdTh), hippocampus, and right anterior temporal, medial parietal, and posterior cingulate cortex in all patients. In a separate analysis, changes in depressive symptoms were associated with RSFC changes in the dorsal ACC, mdTh, putamen, medial prefrontal, and lateral parietal cortex. RSFC of these regions did not change in healthy controls. CONCLUSIONS: Neuroplasticity underlying clinical change was in part separable from changes associated with the effects of ECT observed in all patients. However, both ECT and clinical change were associated with RSFC modulation in dorsal ACC, mdTh and hippocampus, which may indicate that these regions underlie the mechanisms of clinical outcome in ECT and may be effective targets for future neurostimulation therapies.